Water temperature effect on sand transport by size fraction in the lower Mississippi River - Akalin, Suleyman, author; Julien, Pierre Y., advisor; Rugg, James F., committee member; Watson, Chester C., committee member; Wohl, Ellen E., committee member (Colorado State University. Libraries, 2002)
Sediment transport characteristics in large alluvial rivers are influenced by many variables. In this study, the effects of water temperature on sediment transport by size fraction are investigated in the Lower Mississippi River. The flow and sediment data for this study were collected near the Old River Control Structures Complex (ORCC) on the Lower Mississippi River at water temperatures ranging from 9 °C to 31 °C in 1998. Velocity magnitude and direction data were obtained using an Acoustic Doppler Current Profiler (ADCP). which is an accurate, reliable and easy-to-use high-performance current profiler. The suspended sediment concentrations were measured using a U.S. P-63 suspended sediment sampler, which is a common depth-integrating, discharge-weighted sampler. Bed material gradation samples were obtained using a drag bucket, which collects samples from the top layer of the bed material. First, the analysis of the effect of water temperature on the transport of sediment is investigated by considering the water temperature effect on both the vertical distribution of velocity profiles and the vertical distribution of suspended sediment concentrations. The analysis of the effect of water temperature on the vertical distribution of velocity profiles was based on the fact that water temperature changes both the viscosity of water, v, and possibly the von Karman parameter, K. The analysis of the effect of water temperature on the movement of sediment is made both directly and indirectly. In the direct analysis, the sediment concentration and transport values at different water temperatures are compared. In the indirect analysis, the effect of water temperature on the main parameters affecting the sediment transport characteristics such as the von Karman parameter (K). Rouse number (Ro). and reference sediment concentration (Ca) are observed first, then these effects are deployed into effects of water temperature on sediment transport. Second, sediment transport was analyzed based on the comparison of the measured and calculated suspended sediment concentration profiles by size fractions. Rouse's suspended sediment distribution equation was used to calculate concentration values for comparison with the field measurements by size fractions. Finally, the analysis of the effect of the Coriolis force on the flow direction was accomplished by investigating the relationship between the ratio of the Coriolis acceleration to the gravitational acceleration and the flow direction measurements. The following conclusions were obtained: 1. A change in water temperature somewhat changes the vertical velocity profiles and definitely the vertical distribution of suspended sediment concentration: thus, the suspended sediment transport amount in the Lower Mississippi River. On average, a water temperature increase of 1 °C causes approximately a 3.09 percent decrease in the suspended sand transport. When the individual sand size fractions are considered, there are about a 2.79. 3.40. 1.42 and 1.49 percent decrease in the suspended very fine. fine, medium and coarse sand transport, respectively. 2. The average sediment concentration decreases with water temperature regardless of sediment size, but the sand concentration decreases more than the silt and clay concentration with the same range of water temperature change. While, on average. suspended sand concentration decreases by approximately 2.00 percent, suspended silt and clay concentration drops off by only 0.35 percent with a 1 °C increase in water temperature. As far as the individual sand fractions are concerned, a change in water temperature influences the fine and very fine sand fractions the most. There is about 2.48 and 1.40 percent decrease in the suspended fine and very fine sand concentration, respectively, with a water temperature rise of 1 °C. 3. The reference sediment concentration near the riverbed is also affected by water temperature change. This conclusion mainly results from the analysis of the fine and very fine sand concentrations because the amounts of both the coarse and medium sand near the riverbed are relatively low. With a water temperature increase of 1 °C. there is about a 1.69 and 0.90 percent decrease in the fine and very fine sand concentrations near the riverbed, respectively. 4. Both the calculated and measured Rouse numbers are the same for very fine sand. As the sand size increases however, there is a difference between the calculated and measured Rouse numbers: the calculated Rouse number values being a lot higher than the measured ones for coarse sand. For example, the calculated Rouse number for coarse sand is approximately 6.5 times higher in February and 3.5 times higher in August than the measured Rouse number. 5. There is a water temperature effect on the flow characteristics, also. Flow velocity and the von Karman parameter decrease slightly with water temperature. While the flow velocity drops off by about 0.66 percent when the water temperature is increased by 1 °C. there is approximately a 2.17 percent rise in the von Karman parameter value in the main flow region as a result of the same range of water temperature increase. 6. There is no clear indication of w whether the flow direction in the Lower Mississippi River is influenced by the Coriolis force or not. Although a theoretical analysis indicates that the Coriolis acceleration is not negligible compared to the downstream gravitational acceleration, the variability in the field measurements does not allow substantiating the theoretical results.
Keywords: civil engineering; hydrology; hydrologic sciences